Poetry New Zealand Yearbook 2 - (:unkn) unknown (Massey University School of English and Media Studies)
Poetry NZ, New Zealand’s longest-running poetry magazine, showcases new writing from this country and overseas. It presents the work of talented newcomers and developing writers as well as that of established leaders in the field. This issue features the poetry of Robert Sullivan, of Māori (Ngā Puhi – Ngāti Manu/Ngāti Hau – & Kāi Tahu) and Galway Irish descent. He is the Head of the School of Creative Writing at Manukau Institute of Technology in South Auckland, and has published seven poetry collections to date.
Keywords: poetry; New Zealand; Poetry New Zealand